Work-related stress among financial professionals: The impact of age, work experience and education. - Talgat Kutebayev; Zhanna Utaliyeva; Marina Sautenkova; Gulnara Aizhanova (PLoS ONE)
Objective The aim of this study was to investigate the differences in the level and sources of work-related stress among financial professionals regarding age, work experience, and educational level. Methods A cross-sectional research design was employed among 702 financial professionals in Kazakhstan who worked in different corporate and government organizations. Data on work-related stress were collected via online questionnaires using the Job Stress Survey (JSS). Results The results showed that young financial professionals experienced higher stress than older professionals due to the lack of opportunity for advancement. Moreover, the study findings revealed that less experienced financial professionals reported higher levels of stress than more experienced professionals due to the meeting deadlines and conflicts with other departments. The study also found that financial professionals with a postgraduate degree stressed more than professionals with an undergraduate degree on major JSS scales. Furthermore, financial professionals with a postgraduate degree experienced higher stress due to the assignment of disagreeable duties, working overtime, lack of opportunity for advancement, inadequate support by supervisor, dealing with crisis situations, lack of recognition for good work, difficulty getting along with supervisor, insufficient personnel to adequately handle an assignment, lack of participation in policy-making decisions, inadequate salary, excessive paperwork, and covering work for another employee than professionals with undergraduate and vocational degrees. Conclusion The findings of this study provide valuable insights for organizations to eliminate and alleviate work-related stress.